The Smurfs 2 [videorecording (DVD)] - Mays, Jayma, 1979-; Perry, Katy ([publisher not identified], 2013)
The evil wizard Gargamel creates a couple of mischievous Smurf-like creatures called the Naughties. But when he discovers that only a real Smurf can give him what he wants, and only a secret spell that Smurfette knows can turn the Naughties into real Smurfs, Gargamel kidnaps Smurfette and brings her to Paris. It's up to Papa, Clumsy, Grouchy, and Vanity to return to our world, reunite with their human friends Patrick and Grace Winslow, and rescue her.